Preneoplastic cells switch to Warburg metabolism from their inception exposing multiple vulnerabilities for targeted elimination - Myllymäki, Henna; Kelly, Lisa; Elliot, Abigail M.; Carter, Roderick N.; Johansson, Jeanette Astorga; Chang, Kai Yee; Cholewa-Waclaw, Justyna; Morton, Nicholas M.; Feng, Yi (Oncogenesis (New York, NY), 2024)
Otto Warburg described tumour cells as displaying enhanced aerobic glycolysis whilst maintaining defective oxidative phosphorylation (OXPHOS) for energy production almost 100 years ago [ 1 , 2 ]. Since then, the ‘Warburg effect’ has been widely accepted as a key feature of rapidly proliferating cancer cells [ 3 – 5 ]. What is not clear is how early “Warburg metabolism” initiates in cancer and whether changes in energy metabolism might influence tumour progression ab initio. We set out to investigate energy metabolism in the HRAS G12V driven preneoplastic cell (PNC) at inception, in a zebrafish skin PNC model. We find that, within 24 h of HRAS G12V induction, PNCs upregulate glycolysis and blocking glycolysis reduces PNC proliferation, whilst increasing available glucose enhances PNC proliferation and reduces apoptosis. Impaired OXPHOS accompanies enhanced glycolysis in PNCs, and a mild complex I inhibitor, metformin, selectively suppresses expansion of PNCs. Enhanced mitochondrial fragmentation might be underlining impaired OXPHOS and blocking mitochondrial fragmentation triggers PNC apoptosis. Our data indicate that altered energy metabolism is one of the earliest events upon oncogene activation in somatic cells, which allows a targeted and effective PNC elimination.